Beyond Carvings and Rituals: Unveiling the Ikenga's Role in Modern Igbo Society - Ndubuisi, Chinyere (Journal of Contemporary Rituals and Traditions, 2024)
Purpose of the Study: This study examines the contemporary significance of the Ikenga, a crucial cultural symbol among the Igbo people of Nigeria, commonly associated with strength, determination, and entrepreneurial drive. Methodology: The study used a qualitative research design and employed semi-structured interviews, participant observation, and document analysis to collect data from various participants in Igbo society. These participants included entrepreneurs, community leaders, cultural historians, and spiritual leaders. Main Findings: The research reveals that Ikenga continues to serve as a significant cultural icon, supporting entrepreneurship and symbolizing communal achievements and personal aspirations in contemporary times. Despite the challenges of globalization, Ikenga adapts to maintain its relevance, underpinning socio-economic practices and embodying the enduring Igbo values of resilience and determination. Applications of this Study: The findings provide valuable insights for policymakers, cultural practitioners, and scholars, highlighting the importance of integrating cultural heritage into development strategies. This study encourages a multidisciplinary approach to understanding the dynamic interplay between traditional symbols and modern societal roles, offering a model for preserving cultural identity in rapidly changing environments. Novelty/Originality of this Study: This research contributes to the ethnographic literature by offering a contemporary analysis of Ikenga's relevance in Igbo society, beyond its traditional and symbolic interpretations. It underscores the symbol's adaptability and enduring significance, enriching the discourse on the preservation of cultural heritage in the face of globalization and modern challenges.